If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(-5k + -7) = 84 Reorder the terms: -7(-7 + -5k) = 84 (-7 * -7 + -5k * -7) = 84 (49 + 35k) = 84 Solving 49 + 35k = 84 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-49' to each side of the equation. 49 + -49 + 35k = 84 + -49 Combine like terms: 49 + -49 = 0 0 + 35k = 84 + -49 35k = 84 + -49 Combine like terms: 84 + -49 = 35 35k = 35 Divide each side by '35'. k = 1 Simplifying k = 1
| 5(k-3)=(k-5) | | (7x-15)1/3 | | 6(5/9) | | F(x)=(-6)+3 | | -1+20n+15=8n-10+6 | | 70-a=25 | | .05x+09(28000-x)=2400 | | -2+b=3 | | 52x=1/625x | | q=50-2p | | -1+20n+3=8n-10+6 | | 2y+3x+1=0 | | 9=-r | | 12x^2-6x=45 | | b+8b+1=19 | | 0=16t^2-40t-25 | | 100=(65000)x(1+0.016)100 | | r+r+8=14 | | -4(3(-5)-5)= | | F(x)=(x+5)-6 | | -4+35y-1=21y+18+5 | | (21y^5-5y^4-18y^3)/(3y^4) | | 3x-4x+5x-9x= | | f(x)=x^2-16x+67 | | r+r+8=6 | | =(65000)x(1+0.016)100 | | 6a-1=17 | | (y-3)(y-3)=2y^2+2y-12 | | s(t)=-16t^2+20t+6 | | H(x)=25-y | | 2x-5x+5=10 | | t=240t-16t^2 |